Mutually commutated converter equipped with thyristor-based cycloconverter - Zhao, Shuang (My University, 2008)
The switching losses of power conversion systems can be significantly reduced by use of the proposed mutually commutated converter topologies which equipped with IGBT-based cycloconverters and permit soft switching of all semiconductor valves in all operating points without any auxiliary valves. However, due to the inherent properties, thyristors are more suitable and attractive for such naturally commutated converters. A simplified three phase power conversion system is studied in this thesis where the load side is represented by counter-emf. The aim of the thesis is to find a feasible way which allows the thyristor-based cycloconverter to be commutated at any instant of each modulation interval. With this purpose, the method should be able to overcome the inherit limitation of the thyristor, which is the lack of turn-off capability. A proposed modulation method named “current clamping control strategy” for wind farms is studied and analyzed using in different operating points in this thesis. Furthermore, the cascaded topology is discussed to show the superiority with respect to the total harmonic distortion.
Keywords: Elkraftteknik; Electric power engineering